New tungsten-based thermal spray coating and thermal spray material for obtaining same

By using a thermal spray coating material containing tungsten, silicon and boron, a glass phase with low softening points is formed to enhance adhesion and reduce cracks, the problem of insufficient durability of quartz electronic devices in the prior art is solved, and the durability and mechanical properties of the thermal spray coating are significantly improved.

JP7657199B2Active Publication Date: 2025-04-04TOCALO CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022504451
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-06
Filing Date
2021-03-04
Publication Date
2025-04-04
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

The prior art quartz electronic devices using halogen gases such as chlorofluorocarbons are insufficient in durability, and dust is easily generated due to physical sputtering or chemical reactions, which affects the yield and quality of semiconductor chip manufacturing.

Method used

The thermal spray coating material containing tungsten, silicon and boron is used to form a coating through air spraying technology, with tungsten as the matrix and silicon and boron oxide as the dispersed phases, forming a glass phase with low softening points to enhance adhesion and reduce cracks.

Benefits of technology

It significantly improves the durability and mechanical properties of thermal spray coatings, reduces cracks and falls caused by physical and chemical splashes, enhances corrosion resistance to halogen gases such as chlorofluorocarbons, and improves the yield and quality of semiconductor chip manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657199000003
    Figure 0007657199000003
  • Figure 0007657199000004
    Figure 0007657199000004
  • Figure 0007657199000005
    Figure 0007657199000005
Patent Text Reader

Abstract

Provided are: a novel tungsten-based thermal-sprayed coating suitable as a member for a plasma etching device that uses a halogen gas; and a thermal-spraying material for obtaining the thermal-sprayed coating. The thermal-sprayed coating is characterized by containing tungsten as a matrix phase and containing an oxide including silicon and boron as a dispersed phase. The plasma etching device member has this thermal-sprayed coating. The thermal-spraying material is characterized by including 1 to 7 wt% of silicon, 0.5 to 3 wt% of boron, and tungsten and unavoidable impurities as the balance. A method for producing the thermal-sprayed coating includes spraying the thermal-spraying material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel tungsten-based thermal spray coating suitable for use as a member for a plasma etching apparatus using a halogen gas, and a thermal spray material for obtaining the thermal spray coating. [Background technology]

[0002] Plasma etching in semiconductor manufacturing is used in the step of creating circuits on wafers. Before plasma etching begins, the wafer is coated with a photoresist or hard mask (usually oxide or nitride) and exposed to the circuit pattern during photolithography. Plasma etching removes only the material after the pattern is traced, and this patterning and etching sequence is repeated multiple times in the semiconductor chip manufacturing process. Plasma etching removes material not only by the physical sputtering effect, but also by the chemical sputtering effect by exposing the wafer to plasma using halogen gases such as fluorine and chlorine.

[0003] In plasma etching, in order to form today's highly integrated semiconductor circuits, it is necessary to create a nearly vertical profile, and high-energy ions and radicals are emitted from the plasma at high density. As a result, not only the wafer to be etched but also the material that constitutes the inner surface of the chamber in which the etching is performed is affected and worn away by the plasma irradiation. As a result, the products generated in this way adhere to the wafer circuits, which is one of the factors that reduces the yield in semiconductor chip manufacturing.

[0004] The material constituting the chamber in which the plasma etching is performed is usually a metal material such as an aluminum alloy, and is not highly resistant to exposure to halogen-based gas plasma. In contrast, ceramic materials such as metal oxides have a complex crystal structure and are highly chemically stable, so they are expected to exhibit good durability against exposure to plasma. Patent Document 1 proposes a method of suppressing damage by forming a thin film of aluminum oxide by sputtering on the inner surface of a quartz observation window in a reaction tank of a CVD device using plasma.

[0005] Patent Document 2 discloses that a coating of aluminum oxide or yttrium oxide is formed on the inner wall of a plasma etching chamber by a thermal spraying method or the like to suppress dust generation due to wear and improve the yield of semiconductor chip manufacturing in the plasma etching process. Furthermore, Patent Document 3 proposes, for the same purpose, to select a coating material for thermal spraying from compounds of various lanthanoid metals and iridium, etc. In addition, since gases whose main chemical reaction sources are oxygen and fluorine are often used as plasma gases in many cases, Patent Documents 4 and 5 disclose that oxyfluorides of rare earth metals such as yttrium are effective as protective coatings.

[0006] On the other hand, in recent years, semiconductors used in advanced technology fields have become increasingly highly integrated, and the line width of the circuits formed on the chips is becoming thinner at an accelerating rate. For this reason, the allowable size of dust in the etching process is now at or below the level of several tens of nm, and furthermore, it is required that the number of allowable dust particles be minimized as much as possible. In contrast, the ceramic coating containing rare earth metal oxyfluorides as described above is worn to a certain extent by plasma exposure, and does not fully meet these requirements. Furthermore, Patent Documents 6 and 7 propose a silicon material, which is the same as the wafer material, as a surface modifier for chamber components, which generates fluorides that gasify at room temperature when exposed to fluorine-containing gas plasma, and which can exhaust this fluoride out of the chamber by exhaust. However, the wear rate of silicon materials is fast, and many practical problems remain, such as the need for frequent re-coating work. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 09-95764 [Patent Document 2] Japan Special Publication No. 2011-528755 [Patent Document 3] Japan Special Publication No. 2012-508467 [Patent Document 4] Japan Special Publication No. 2012-508684 [Patent Document 5] Japanese Patent Publication No. 2014-009361 [Patent Document 6] Japanese Patent Publication No. 2007-250569 [Patent Document 7] Japanese Patent Publication No. 2018-48378 Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above circumstances, an object of the present invention is to provide a novel thermal spray coating that is suitable as a material capable of effectively suppressing the generation of dust resulting from physical sputtering, fluorination reactions, and the like that occur when materials of equipment constituting a chamber in which plasma etching using a halogen gas such as fluorine gas is performed in the above-mentioned semiconductor manufacturing process are exposed to plasma; a thermal spray material for obtaining such a thermal spray coating; and a method for producing a thermal spray coating from such a thermal spray material. [Means for solving the problem]

[0009] The present inventors have conducted intensive research to achieve the above object and have arrived at the present invention which is capable of solving the above problem. That is, the present inventors focused on tungsten as a thermal spray material for the above-mentioned purpose, because, like silicon materials, even if it reacts with fluorine gas plasma at room temperature, the fluoride is gasified and easily discharged. Since tungsten is a metal with a very high density, it was thought that the rate of wear due to physical sputtering would be low. However, C.Moreau et.al., "Thermal diffusivity of plasma-sprayed tungsten coating", Surface and Coating technology, 61 (1993), pp. 67-71, reveals that when thermal spraying is performed in the atmosphere using a tungsten raw material, many cracks opening parallel to the interface with the substrate inevitably occur in the coating, and the thermal diffusivity of the thermal spray coating becomes much smaller than that of the bulk body.

[0010] Also, HK Kang, "Thermal properties of plasma-sprayed tungsten deposits", J. of Nuclear Mate. 335 (2004), pp. 1-4, reveals that the cracks are caused by the fact that oxides are easily formed during thermal spraying due to the extremely high melting point of tungsten and its poor oxidation resistance. Tungsten oxides are not very stable, and because they sublime at relatively low temperatures and are brittle, thermal spray coatings containing tungsten oxides are extremely brittle with low mechanical properties, so it is thought that peeling of thin layers is likely to occur due to changes in surface temperature when exposed to plasma.

[0011] The present inventors have discovered that when the thermal spray material contains not only tungsten but also boron and silicon in addition to tungsten, reaction products that become residues are less likely to be produced even when the resulting thermal spray coating is exposed to a plasma gas containing fluorine or oxygen. That is, boron and silicon contained in the thermal spray material are more easily oxidized than tungsten, but unlike tungsten oxide, they can form a protective film that prevents oxygen from penetrating the inner surface of the molten particle. Boron, in particular, has a low oxidation start temperature, and the generated boron oxide melts at 500°C or less and becomes an oxidation protective film for the tungsten-based particles. Specifically, when a material containing boron and silicon together with tungsten is thermally sprayed in the atmosphere, the boron is oxidized, followed by the oxidation of silicon, to form silicon oxide. Silicon oxide then easily bonds with boron oxide, raising the melting point while maintaining a glassy state, and is thought to prevent the oxidation protective film from scattering during the flight of the particles. The thermal spray coating produced in this way has a structure in which tungsten is included as a matrix phase, and furthermore, oxides containing boron and silicon are dispersed. The oxides containing boron and silicon form a glass phase with a low softening point that wets well with tungsten, so there is almost no generation of cracks in the matrix during solidification.

[0012] Thus, the present invention has the following aspects. (1) A thermal spray coating comprising tungsten as a matrix phase and an oxide containing silicon and boron as a dispersed phase. (2) The thermal spray coating according to (1) above, wherein the volume ratio of the dispersed phase is 2 to 6% based on the total amount of the matrix phase and the dispersed phase. (3) The thermal spray coating according to (1) or (2) above, wherein the matrix phase contains silicon and / or boron. (4) The thermal spray coating according to any one of the above (1) to (3), wherein the dispersed phase contains tungsten. (5) The thermal spray coating according to any one of the above (1) to (4), having a thickness of 50 to 1000 μm. (6) A member for a plasma etching apparatus having the thermal spray coating according to any one of (1) to (5) above. (7) The member for a plasma etching apparatus according to (6) above, wherein the plasma etching apparatus is a dry etching apparatus using a gas plasma containing fluorine.

[0013] (8) A thermal spray material comprising 1 to 7 weight percent silicon, 0.5 to 3 weight percent boron, and the remainder being tungsten and unavoidable impurities. (9) The thermal spray material according to (8) above, which contains 2 to 5% by weight of silicon and 1.5 to 3% by weight of boron. (10) Tungsten, silicon and boron, W5Si x B y (8) or (9) above, wherein the thermal spray material mainly comprises a tungsten-silicon-boron ternary compound represented by the formula (1): (wherein x is 0.8 to 1.7, and y is 1.3 to 2.2). (11) The tungsten-silicon-boron ternary compound is W5SiB2 and / or W5Si 1.5 B 1.5 The thermal spray material according to (10) above, which is a compound represented by the formula: (12) The thermal spray material according to any one of (8) to (11) above for producing the thermal spray coating according to any one of (1) to (5) above. (13) A method for producing a thermal spray coating by thermal spraying the thermal spray material according to any one of (8) to (12) above. (14) A method for producing a thermal sprayed coating as described in (13) above, in which the thermal spraying material is thermally sprayed by atmospheric plasma spraying. (15) A method for producing a thermal sprayed coating according to the above (13) or (14), which comprises producing a thermal sprayed coating according to any one of the above (1) to (5). Effect of the Invention

[0014] According to the present invention, there is provided a thermal spray coating that is suitable for formation in a chamber subjected to dry etching with a fluorine-containing gas plasma and that can suppress dust generation during the process. Also, according to the present invention, there is provided a thermal spray material for obtaining the above-mentioned thermal spray coating, particularly by atmospheric plasma spraying. Furthermore, the present invention provides a material suitable for use as a member for a plasma etching apparatus, such as a chamber used for dry etching with a fluorine-containing gas plasma. [Brief description of the drawings]

[0015] [Figure 1a] The cross-sectional structure of the coating of Example 1 and the locations (a, b, c, d) where the component analysis was performed are shown. [Figure 1b] The cross-sectional structure of the coating of Comparative Example 1 and the locations (e, f, g, h) where the component analysis was performed are shown. [Figure 1c] The cross-sectional structure of the coating of Comparative Example 2 and the locations (i, j, k, l) where the component analysis was performed are shown. [Diagram 2] The results of the Suga abrasion test for the thermal spray coatings of Example 1 and Comparative Examples 1 and 2 are shown. [Diagram 3] 1 shows an outline of a parallel plate type dry etching apparatus used in plasma exposure tests of the thermal sprayed coatings of Example 1 and Comparative Examples 1 and 2. [Figure 4] The results of a plasma exposure test of the thermal spray coatings of Example 1 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] (Thermal spray coating) The thermal spray coating of the present invention contains tungsten as a matrix phase (hereinafter also simply referred to as the matrix), and contains an oxide containing silicon and boron as a dispersed phase. Tungsten, which forms the matrix that is the main constituent phase of the thermal spray coating of the present invention, has a high specific gravity and is known to be the metal with the largest atomic bond energy, and is highly resistant to physical sputtering. Furthermore, the boiling point of tungsten hexafluoride, a compound of tungsten and fluorine, is 17.5°C and gasifies at the temperature at which semiconductor dry etching is performed.

[0017] The tungsten matrix in the thermal spray coating can contain silicon and / or boron. In this case, silicon and / or boron may be dissolved in tungsten, or may be dispersed as fine tungsten silicide or tungsten boride. Silicon, like tungsten, is a component whose reaction product with fluorine vaporizes at room temperature or below, and boron is also a component that is easily gasified, so it does not interfere with the characteristics of tungsten as a plasma-resistant protective coating material. When the matrix contains silicon, the silicon content is preferably 0.2 atomic % or more, and on the other hand, is preferably 15 atomic % or less, and more preferably 10 atomic % or less, based on the total amount of the matrix. Furthermore, when the matrix contains boron, the boron content is preferably 0.5 atomic % or more, and more preferably 20 atomic % or less, and more preferably 15 atomic % or less, relative to the total amount of the matrix. By including silicon and / or boron in tungsten, the mechanical properties such as hardness of the coating are improved, but if the above range is exceeded, the rate of wear by plasma increases.

[0018] In thermal spray coatings formed from thermal spray raw materials consisting only of tungsten, the molten thermal spray raw material droplets are usually partially oxidized before being deposited on the substrate, forming extremely unstable tungsten oxides. Because this tungsten oxide is brittle, large-scale cracks parallel to the substrate interface are generated in the coating due to thermal stresses that occur during cooling. When cracks occur, thermal or mechanical stresses are generated in the thermal spray coating, causing internal cracks to develop in the coating or chipping off of surface portions of the coating. On the other hand, in a thermal spray coating formed from a thermal spray raw material containing silicon and boron as well as tungsten, the amount of brittle tungsten oxide is small and the particle size is small, so that the thermal spray coating obtained does not easily develop large cracks or become partially chipped even when thermal and mechanical stress occurs.

[0019] The oxides containing silicon and boron contained as the dispersed phase in the thermal spray coating of the present invention are prone to eutectic formation, and form a glass phase at a high cooling rate during thermal spray coating formation, and in many cases exist as amorphous particles with an average particle size of 100 μm or less. The tungsten matrix and the glass phase consisting of the oxides containing silicon and boron are well bonded, and no cracks or pores are generated at the interface. In addition, the softening temperature of the glass phase consisting of the oxides containing silicon and boron is relatively low, and when the surface temperature of the coating increases during coating formation by thermal spraying or exposure to plasma, etc., and thermal stress is applied, the glass phase softens and relieves the stress.

[0020] The content of the dispersed phase in the thermal spray coating of the present invention is preferably 2% or more and 8% or less by volume with respect to the total amount of the matrix and the dispersed phase. If the volume ratio of the dispersed phase is less than 2%, the amount of remaining tungsten oxide increases and it becomes difficult to function as a stress relaxation phase. On the other hand, if the volume ratio of the dispersed phase exceeds 8%, the physical sputtering resistance of the entire coating is significantly reduced. In particular, the content of the dispersed phase is more preferably 3% or more and more preferably 6% or less by volume.

[0021] The dispersed phase is preferably a binary system consisting of oxides of silicon and boron, but may also contain oxides of tungsten and / or rare earth elements, such as scandium, yttrium, lanthanum, cerium, neodymium, samarium, gadolinium, erbium, ytterbium, and lutetium. When tungsten is contained in the dispersed phase, the content of tungsten is preferably 3 atomic % or more, and more preferably 30 atomic % or less, and more preferably 25 atomic % or less, based on the total amount of the dispersed phase. The content of rare earth elements is preferably 1 to 6 atomic %, and more preferably 2 to 4 atomic %, based on the total amount of the dispersed phase. By adding an appropriate amount of tungsten or rare earth elements to the dispersed phase, the glass temperature and softening temperature can be adjusted.

[0022] The thermal spray coating of the present invention has a thickness of preferably 50 to 1000 μm, more preferably 100 to 500 μm. In the present invention, a thermal spray coating having a thickness in this range can be easily obtained, and the thermal spray coating having this thickness is suitable as a protective coating for covering a chamber member to be subjected to fluorine-containing plasma dry etching of a semiconductor. This is because a protective coating that is unavoidably exposed to plasma is required to have resistance to both physical sputtering and chemical sputtering. Since damage to a protective coating by plasma causes minute defects in semiconductor products, the requirements for a protective coating have become significantly higher with the increase in semiconductor integration. One of the coatings that meets this requirement is a coating that has high resistance to physical sputtering, and even if wear occurs due to physical sputtering, the wear reacts with a halogen component to become a gas that is easily discharged. The thermal spray coating of the present invention can fully meet the above requirements.

[0023] (Thermal spray material) The thermal spray coating of the present invention is produced by thermal spraying of a thermal spray material containing tungsten, silicon and boron. The thermal spray material is preferably in the form of powder or particles. The thermal spray material may be any of a single compound, a compound consisting of multiple elements, or a metal powder, or a combination of these may be selected. As the thermal spray material for forming the thermal spray coating, a mixture of individual powders of tungsten, silicon, and boron, each mixed to have the content in the resulting thermal spray coating, can be used. The thermal spray material is not limited to the mixed powder, and a binary compound powder of silicon disilicide as the silicon source and tungsten boride as the boron source can be used. Furthermore, a ternary compound powder of tungsten-silicon-boron can also be used. A mixture of these compounds and / or single element powders can also be used.

[0024] The thermal spray material in the present invention contains tungsten as a main component, silicon, and boron. In particular, in order to make the volume ratio of the glass phase containing oxides of silicon and boron in the obtained thermal spray coating 2-8% relative to the total of the matrix and glass phase, the silicon content in the thermal spray material is preferably 1-7% by weight, more preferably 2-5% by weight, and the boron content is preferably 0.5-3% by weight, more preferably 1.5-3% by weight.

[0025] If the silicon content is 1% by weight or less, the glass phase dispersed in the coating after thermal spraying is reduced, and the effect is not easily exhibited. On the other hand, if the silicon content exceeds 7% by weight, a large amount of brittle tungsten silicide is precipitated in the coating after thermal spraying, and the coating is likely to crack or peel off. On the other hand, if the boron content exceeds 3% by weight, a large amount of brittle tungsten boride is precipitated in the coating after thermal spraying, and the coating is likely to crack or peel off. Also, if the boron content is 0.5% by weight or less, the glass phase dispersed in the coating after thermal spraying is reduced, and the effect is not easily exhibited.

[0026] In the present invention, the thermal spray material is preferably a powder of a ternary compound of tungsten, silicon and boron in order to obtain macroscopic uniformity of the thermal spray coating. x B y Preferably, the composition is as follows: where x is preferably 0.8 to 1.7, more preferably 0.9 to 1.6, and y is preferably 1.3 to 2.2, more preferably 1.4 to 2.1. In particular, W5Si 1.5 B 1.5 , or W5SiB2 is preferred.

[0027] (Method of manufacturing thermal spray coating) The thermal spray coating of the present invention can be produced by a known thermal spraying method using the above-mentioned thermal spray material, but it can be preferably produced by the following procedure. The above-mentioned spray materials of the thermal spray coating, such as compound powders and / or metal powders, are weighed out and mixed and pulverized in an organic solvent such as alcohol using a rotary ball mill or a vibrating ball mill. These raw powders are preferably as pure and fine as possible in order to obtain a thermal spray coating with excellent properties. In particular, in order to ensure the homogeneity of the obtained thermal spray coating, the average particle size (D50) of the compound powder is preferably 10 μm or less, more preferably 5 μm or less, and of these, 1 to 3 μm is preferred.

[0028] The raw powder pulverized and mixed by a rotary ball mill, a vibrating ball mill, or the like may be used as the thermal spray material as it is, but it is preferable to use an organic binder and perform a granulation process using a spray dryer or the like in a non-oxidizing atmosphere. As the organic binder, it is preferable to select one that is easily removed during sintering, and acrylic resin, polyethylene glycol, etc. can be used.

[0029] The powder that has undergone the granulation process is generally spherical and has good fluidity, but in order to give the powder strength sufficient to withstand transportation by pressurized gas or the like, it is preferable to calcinate the granulated powder in a non-oxidizing atmosphere such as argon at preferably 1000 to 1800°C, more preferably 1200 to 1600°C. This removes the organic binder and allows the primary particles in the granulated powder to be sintered together while maintaining their spherical shape. If the powder is then crushed, it becomes roughly spherical and does not easily crumble even when transported by pressurized gas.

[0030] The obtained sintered granulated powder is preferably classified to a desired particle size and then used as a thermal spray raw material. The average particle size (D50) of the thermal spray raw material powder is preferably 10 to 100 μm, more preferably 15 to 75 μm. As the plasma working gas, argon, nitrogen, helium, hydrogen, etc. can be used. Among them, it is preferable to use a mixed gas such as argon-hydrogen or nitrogen-hydrogen, taking advantage of the characteristics of each gas. The thermal spray output, defined as the product of the operating voltage and the operating current, is in the range of about 20 to 100 kW and can be selected according to the type and size of the thermal spray material and the substrate. In addition, the thermal spray distance, which is the distance between the plasma gun and the thermal spray target, is preferably set between about 50 mm and about 200 mm according to the thermal spray material and the thermal spray conditions.

[0031] The thermal spraying method used in the present invention is preferably a thermal spraying method using plasma, such as an atmospheric plasma spraying method or a reduced pressure plasma spraying method, and in particular, an atmospheric plasma spraying method is preferred. EXAMPLES

[0032] The present invention will be specifically described below with reference to examples of the present invention, but the present invention is not limited to these examples. The atmospheric plasma spraying apparatus and spraying conditions used in the following Examples and Comparative Examples are as follows: Thermal spraying equipment: Sluzer Metco, 9MB Operating voltage: 65V Operating current: 700A Primary gas (Ar) flow rate: 60NL / min Secondary gas (H2) flow rate: 5NL / min Spray distance: 140mm

[0033] Example 1 Tungsten powder (manufactured by Japan New Metals, particle size: 1.5-2.0 μm), tungsten boride powder (manufactured by Japan New Metals, particle size: 3-6 μm), and tungsten silicide powder (manufactured by Japan New Metals, particle size: 2-5 μm) were weighed out to the prescribed contents shown below, and mixed and pulverized using a rotary ball mill with ethanol as a solvent to produce a slurry. This slurry was used as a raw material and granulated using a spray dryer, and heated to 1600°C in argon gas to produce a porous spherical powder containing 3.5% by weight of silicon, 2.2% by weight of boron, and inevitable impurities. The particle size of this spherical powder was 15-75 μm.

[0034] The spherical powder prepared above was used as the spray material to form a spray coating having a thickness of about 0.2 mm on one side of the surface (surface roughness Ra: 2-5 μm) roughened by sandblasting of two substrates X and Y, both of which were made of aluminum alloy (A5052), using the above-mentioned atmospheric plasma spraying device under the above-mentioned spraying conditions. The two substrates X and Y were square plates with dimensions of [50 mm length, 50 mm width, 3 mm thickness] and [20 mm length, 20 mm width, 5 mm thickness], respectively.

[0035] The cross-section of the thermal spray coating formed on the above-mentioned substrate X (thermal spray sample) was observed and its components were analyzed. The cross-section was exposed using a cross-session polisher (SM-09010, manufactured by JEOL Ltd.), and the cross-section was observed using a field emission scanning electron microscope (JSM-7200F, manufactured by JEOL Ltd.), and the components were analyzed by energy dispersive X-ray analysis (EDX). Figure 1a shows the cross-sectional structure of the thermal spray coating and the points (a, b, c, d) where the component analysis was performed. The cross section has a structure in which dispersed particles are arranged in a matrix structure, and as shown in Table 1, the composition (unit: atomic %, the same below) of the matrix (analysis points a and b) was 87-89% tungsten, 3-8% boron, and 5-8% oxygen, while the dispersed phase (analysis points c and d) was 4-20% tungsten, 12-21% silicon, 15-16% boron, and 53-59% oxygen.

[0036] [Table 1]

[0037] On the other hand, the above-mentioned substrate Y (sprayed sample) was ultrasonically cleaned in pure water and dried in a thermostatic chamber maintained at 85°C, and then the ease with which particles would fall off from the coating due to mechanical stress was evaluated using the Suga abrasion test method as follows. Note that the surface of the sprayed sample used in this test was left in its as-sprayed state without polishing or other treatment. In the Suga abrasion test, the thermal sprayed surface of a flat specimen is pressed against the outer circumferential surface of a disk with abrasive paper attached at a constant load and slid back and forth. The abrasive grains of the abrasive paper scratch the thermal sprayed surface, so if there are open cracks, the thermal sprayed coating will wear down significantly. The test was performed using abrasive paper made of #180 SiC abrasive grains and a pressing force of 15 N. Figure 2 shows the test results, and it can be seen that the increase in the amount of wear of the coating of Example 1 with respect to the number of sliding strokes is very gradual, and the amount of wear is significantly less than that of the samples of Comparative Examples 1 and 2 described below.

[0038] The sprayed surface of the above substrate Y (sprayed sample) was polished with #800 wet emery paper, ultrasonically cleaned in pure water, and then dried in a thermostatic chamber at 85°C before being subjected to a plasma exposure test. For the test, a parallel plate type dry etching device as shown in Figure 3 was used, and the sprayed sample was placed on a silicon wafer placed on the cathode side with the sprayed surface facing the anode, and exposed to plasma. There were two plasma generation conditions: A, which allows evaluation of resistance to chemical sputtering, and B, which allows evaluation of resistance to physical sputtering, and the respective conditions were as follows:

[0039] Condition A: Plasma gas species and flow rate: CF4...50sccm, O2...10sccm, Ar···50sccm RF output: 800W, Bias: 600W Condition B: Plasma gas species and flow rate: O2...10sccm, Ar...100sccm RF output: 1000W, Bias: 1000W

[0040] The results of the plasma exposure test are shown in Fig. 4, with the wear rate of Comparative Example 1 described below taken as 100. The wear rate of Example 1 was smaller than that of either plasma condition A or B, and its superiority is particularly remarkable under conditions where wear due to physical sputtering is the main factor.

[0041] (Comparative Examples 1 and 2) In Comparative Example 1, powder (tungsten: 99.8 mass% and unavoidable impurities, particle size: 10 to 40 μm, manufactured by Japan New Metals Co., Ltd., WL) was used as the thermal spray material. In Comparative Example 2, powder (tungsten: 91.6 mass% and silicon: 8.4 mass%, W5Si3 compound (average particle size (D50): 12.5 μm, manufactured by Japan New Metals Co., Ltd.) was used. Then, by the atmospheric plasma spraying method under the same conditions as in Example 1, thermal spray coatings were formed on the surfaces roughened by sandblasting of two substrates X and Y having the same shape as in Example 1. Cross-sectional observation and component analysis of the thermal sprayed coatings of Comparative Examples 1 and 2 formed on the above-mentioned substrate X (thermal spray sample) were performed in the same manner as in Example 1. Figure 1b shows the cross-sectional structure of the thermal sprayed coating of Comparative Example 1 and the locations (e, f, g, h) where the component analysis was performed, and Figure 1c shows the cross-sectional structure of the thermal sprayed coating of Comparative Example 2 and the locations (i, j, k, l) where the component analysis was performed.

[0042] The cross section of the sprayed film in Comparative Example 1 had a nearly uniform structure with many coarse cracks, as shown in Fig. 1b. As shown in Table 2, the composition of the matrix (analysis points e and f) was 92-95% tungsten and 5-8% oxygen, while the thin layer on the inner surface of the crack (analysis points g and h) was 17-22% tungsten and 78-83% oxygen. The cross section of the sprayed film in Comparative Example 2 also had a nearly uniform structure with many coarse cracks, as shown in Fig. 1c. As shown in Table 2, the composition of the matrix (analysis points i and j) was 93-96% tungsten and 4-7% oxygen, while the thin layer on the inner surface of the crack (analysis points k and l) was 12-20% tungsten, 65-73% oxygen, and 7-23% silicon. The results in Table 2 show that the thermal sprayed coatings of Comparative Examples 1 and 2 are composed of tungsten and tungsten oxide, and that large cracks originate from the tungsten oxide.

[0043] [Table 2]

[0044] The ease with which particles fall off from the coating due to mechanical stress was evaluated for substrate Y (thermal spray sample) having the thermal spray coatings of Comparative Examples 1 and 2 using the Suga abrasion test method under the same conditions as for the thermal spray coating of Example 1. The test results are shown in Figure 2, and it was found that the amount of abrasion of the comparative coating was 5 to 6 times that of the examples.

[0045] Substrate X (sprayed sample) having the sprayed coating of Comparative Examples 1 and 2 was subjected to a plasma exposure test similar to that of Example 1. The results of the plasma exposure test are shown in FIG. 4, with the wear rate of Comparative Example 1 taken as 100. Under both plasma conditions A and B above, the wear rate of substrate X was greater than that of Example 1, and the difference was particularly noticeable under condition B, where wear was mainly due to physical sputtering. [Industrial Applicability]

[0046] The thermal spray coating of the present invention is effective in a wide range of applications, including plasma dry etching chamber components that use halogen gases such as fluorine gas in semiconductor manufacturing processes.

[0047] The entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2020-38841, filed on March 6, 2020, are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]

[0048] 1: Anode 2: Cathode 3: Power supply 4: Wafer 5: Sprayed sample 6: Plasma gas 7: Plasma 8: Exhaust a, b, c, d: Cross-sectional structure of the thermal spray coating of Example 1 (Fig. 1a) and the locations where the component analysis was performed e, f, g, h: Cross-sectional structure and component analysis points of the thermal spray coating of Comparative Example 1 (Fig. 1b) i, j, k, l: Cross-sectional structure and component analysis points of the thermal spray coating of Comparative Example 2 (Fig. 1c)

Claims

1. A thermal spray coating comprising tungsten as a matrix phase and an oxide containing silicon and boron as a dispersed phase, the content of the dispersed phase being 2% or more and 8% or less by volume relative to the total amount of the matrix phase and the dispersed phase.

2. 2. The thermal spray coating according to claim 1, wherein the content of the dispersed phase is 3% or more and 6% or less by volume based on the total amount of the matrix phase and the dispersed phase.

3. The thermal spray coating according to claim 1 or 2, wherein the matrix phase contains silicon and / or boron.

4. The thermal spray coating according to any one of claims 1 to 3, wherein the dispersed phase contains tungsten.

5. The thermal spray coating according to any one of claims 1 to 4, having a thickness of 50 to 1000 µm.

6. A plasma etching apparatus member having the thermal spray coating according to any one of claims 1 to 5.

7. 7. The member for a plasma etching apparatus according to claim 6, wherein the plasma etching apparatus is a dry etching apparatus using a gas plasma containing fluorine.

8. A thermal spray material comprising 1 to 7 weight percent silicon, 0.5 to 3 weight percent boron, and the balance being tungsten and inevitable impurities.

9. 9. The thermal spray material according to claim 8, which contains 2 to 5% by weight of silicon and 1.5 to 3% by weight of boron.

10. Tungsten, silicon and boron are 5 S x B y 10. The thermal spray material according to claim 8, comprising a ternary compound of tungsten, silicon and boron represented by the formula: (wherein x is 0.8 to 1.7, and y is 1.3 to 2.2).

11. The tungsten-silicon-boron ternary compound is W 5 SiB 2 and / or W 5 S 1.5 B 1.5 The thermal spray material according to claim 10, which is a compound represented by the formula:

12. A method for producing a thermal spray coating by thermal spraying the thermal spray material according to any one of claims 8 to 11.

13. The method for producing a thermal spray coating according to claim 12, wherein the thermal spray material is sprayed by air plasma spraying.

Citation Information

Patent Citations

  • Manufacture of ultrahigh temperature oxidation resistant material, ultrahigh temperature oxidation resistant composite material and their green compact

    JP1992235249A

  • Coating film excellent in corrosion resistances to halogen gas and halogen plasma, and laminated structure formed with the coating film

    JP1997095764A

  • Treatment system and corrosion resistant member used therefor

    JP2001226773A

  • Plasma treatment apparatus and member to be exposed in plasma

    JP2007250569A

  • Ceramic coating body with plasma resistance

    JP2011528755A